Hubungan Asupan Kalsium dan Kadar Kalsium dalam Darah dengan Indeks Massa Tubuh pada Mahasiswa Poltekkes Kemenkes Padang - Evynatra Evynatra; Masrul Masrul; Zelly Dia Rofinda (Poltekkes Kemenkes Padang, 2025)
Obesity or being overweight is a global problem that occurs due to improper diet and nutritional intake. The 2023 Indonesian Health Survey (SKI) report showed that the proportion of obesity in the population aged 15-24 years was 16.2%. This study aims to analyze the relationship between calcium intake and blood calcium levels with body mass index in students of the Padang Ministry of Health Polytechnic. The study design used a cross-sectional study with a sample size of 73 students selected randomly. Data were obtained through interviews using the SQ-FFQ sheet, anthropometric measurements, and analysis of blood calcium levels. The results showed that the respondents' BMI was 24.58, the average daily calcium intake was 259.07 mg, far below the daily recommendation of 1000-1200 mg. The average blood calcium levels of respondents were within the normal range (mean 9.71 mg/dL and standard deviation 0.35 mg/dL). Statistical analysis showed a significant negative relationship between calcium intake and Body Mass Index (BMI) (p=0.020), a significant relationship was found between blood calcium levels and BMI (p=0.027). In conclusion, low calcium intake is correlated with an increased risk of obesity. It is recommended to Poltekkes to always have continuity of BMI screening and pay attention to calcium intake education through healthy eating patterns among students and for students who experience calcium deficiency, it is expected to be consulted to the clinic.